2007
DOI: 10.1590/s0004-282x2007000600005
|View full text |Cite
|
Sign up to set email alerts
|

Motor learning processes: an electrophysiologic perspective

Abstract: -The goal of the present study was to investigate electrophysiologic, qEEG, changes when individuals were exposed to a motor task. Subjects' brain electrical activity was analyzed before and after the typewriting training task. For the neurophysiological variable asymmetry, a paired t-test was performed to compare each moment, pre and post-task, in the beta bands. The findings showed a change for the qEEG variable in each scalp site, F3/F4; C3/C4 and P3/P4. These results suggest an adaptation of pre-frontal, s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 30 publications
0
2
0
Order By: Relevance
“…This fits with the proposal that increased visuospatial demands of motor control is seen in amputees (Metzger et al, 2010), and may relate to the findings seen in this study. In the cortex, studies have demonstrated that principally motor cortex, lateral premotor, and the supplementary motor areas (SMA) are commonly involved in motor learning (Hikosaka, Nakamura, Sakai, & Nakahara, 2002;Velasques et al, 2007;Wolpert, Ghahramani, & Flanagan, 2001). However, the introduction of the highly spatial aspect of our task may heighten the involvement of visuospatial mechanisms of control.…”
Section: Discussionmentioning
confidence: 99%
“…This fits with the proposal that increased visuospatial demands of motor control is seen in amputees (Metzger et al, 2010), and may relate to the findings seen in this study. In the cortex, studies have demonstrated that principally motor cortex, lateral premotor, and the supplementary motor areas (SMA) are commonly involved in motor learning (Hikosaka, Nakamura, Sakai, & Nakahara, 2002;Velasques et al, 2007;Wolpert, Ghahramani, & Flanagan, 2001). However, the introduction of the highly spatial aspect of our task may heighten the involvement of visuospatial mechanisms of control.…”
Section: Discussionmentioning
confidence: 99%
“…From this perspective, learning depends on the integrity of the sensorial processing, which is, on the ability of the individual to receive the sensorial information from the environment and from his/her body movements, and to process them and integrate them in the central nervous system (CNS), and utilize them to generate adequate adaptive responses 2 . Previous studies showed that various cortex areas are part of the motor learning process 3,4,5 . Among these areas, the frontal cortex and the somatomotor cortex should be highlighted, since these are the regions that directly participate in motor control.…”
mentioning
confidence: 99%